2020
DOI: 10.1002/pld3.259
|View full text |Cite
|
Sign up to set email alerts
|

Secretion dynamics of soyasaponins in soybean roots and effects to modify the bacterial composition

Abstract: The term "rhizosphere" was coined by L. Hiltner in 1904 and refers to "the zone of soil surrounding the root which is affected by it" (Hartmann, Rothballer, & Schmid, 2008, Hiltner, 1904). Plant roots function as an anchor that supports the plant body and absorb nutrients and water; they also secrete a variety of plant-derived metabolites into the rhizosphere, which include low-molecular weight compounds, such as amino acids, sugars, phenolics, terpenoids, and lipids, and high-molecular weight compounds, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 67 publications
4
57
0
Order By: Relevance
“…In addition to isoflavones, soybean roots secrete an equivalent amount of soyasaponins, which was first demonstrated by Tsuno et al (2018). Recently, soyasaponin Bb was shown to enrich Novosphingobium, commonly found in the soybean rhizosphere (Fujimatsu et al, 2020). The secretion of these specialized metabolites changes dramatically in quality and quantity depending on the developmental stage of the soybean plant (Sugiyama et al, 2016;Tsuno et al, 2018); however, the diurnal regulation of these soybean metabolites remains to be described.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to isoflavones, soybean roots secrete an equivalent amount of soyasaponins, which was first demonstrated by Tsuno et al (2018). Recently, soyasaponin Bb was shown to enrich Novosphingobium, commonly found in the soybean rhizosphere (Fujimatsu et al, 2020). The secretion of these specialized metabolites changes dramatically in quality and quantity depending on the developmental stage of the soybean plant (Sugiyama et al, 2016;Tsuno et al, 2018); however, the diurnal regulation of these soybean metabolites remains to be described.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, also carotene (C40) which plays a role in photosynthesis (Fahy et al, 2005) and saponines which have been shown to modulate soil microbial communities (Fujimatsu et al, 2020), belong to this group. The roots of Cy.…”
Section: Discussionmentioning
confidence: 99%
“…It includes mono (C10) – and sequiterpenoids (C15), which are known for their roles in direct and indirect defence against herbivores and pathogens. In addition, also carotene (C40) which plays a role in photosynthesis (Fahy et al, 2005) and saponines which have been shown to modulate soil microbial communities (Fujimatsu et al, 2020), belong to this group. The roots of Cy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that saponins are secreted from plant roots into the rhizosphere [ 31 , 32 , 33 , 34 ]. Previously, we demonstrated that soyasaponins and α-tomatine were secreted from soybean and tomato roots in both hydroponic and field conditions [ 35 , 36 , 37 ]. Furthermore, both soyasaponins and α-tomatine were found to alter the bacterial communities and increase Sphingomonadaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both soyasaponins and α-tomatine were found to alter the bacterial communities and increase Sphingomonadaceae. Soyasaponins enriched Novosphingobium , whereas tomatine enriched Sphingobium at the genus level [ 35 , 37 ]. Based on these differential effects of the saponins in the soil bacterial communities, we hypothesized a link between saponin identity and soil bacterial community.…”
Section: Introductionmentioning
confidence: 99%